2016
DOI: 10.1016/j.foodchem.2015.07.141
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen dependency of one-electron reactions generating ascorbate radicals and hydrogen peroxide from ascorbic acid

Abstract: The effect of oxygen on the two separate one-electron reactions involved in the oxidation of ascorbic acid was investigated. The rate of ascorbate radical (Asc(-)) formation (and stability) was strongly dependent on the presence of oxygen. A product of ascorbic acid oxidation was measurable levels of hydrogen peroxide, as high as 32.5 μM from 100 μM ascorbic acid. Evidence for a feedback mechanism where hydrogen peroxide generated during the oxidation of ascorbic acid accelerates further oxidation of ascorbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…Recently, it has been shown that small amounts of H 2 O 2 boost LPMO activity, while higher amounts lead to inactivation of the enzyme . The presence of ascorbic acid in the reactions described above will lead to generation of H 2 O 2 , which perhaps could explain the observed apparent enzyme inactivation. It was also shown that inactivation of LPMOs by excess H 2 O 2 is accompanied by oxidative damage in the catalytic center only, with the N‐terminal histidine being especially vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that small amounts of H 2 O 2 boost LPMO activity, while higher amounts lead to inactivation of the enzyme . The presence of ascorbic acid in the reactions described above will lead to generation of H 2 O 2 , which perhaps could explain the observed apparent enzyme inactivation. It was also shown that inactivation of LPMOs by excess H 2 O 2 is accompanied by oxidative damage in the catalytic center only, with the N‐terminal histidine being especially vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the formation of H 2 O 2 in the reaction between AscA and molecular oxygen is well-known (35). Furthermore, the oxidation of AscA by O 2 is catalyzed by metal ions, like Cu(II) (36,37), so that their presence even in trace amounts can significantly affect the formation of H 2 O 2 and interpretation of the results of LPMO kinetics. The problem is further amplified by the occurrence of metal ions in polymeric substrates of LPMOs, such as cellulose and chitin (38 -40).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Their combination appeared to be crucial. A marked protective effect, when oxygen is replaced by argon in a solution containing Cu 2þ ions, was also observed by Boatright (2016). Subsequently, the effect of oxygen deprivation was assessed in the supernatant of centrifuged apple pur ee.…”
Section: Anaerobic Vs Aerobic Degradationmentioning
confidence: 93%
“…However, it is not known if the concomitant presence of oxygen is necessary for the Fe 3þ ion-caused oxidation. Under anaerobic conditions and in the presence of Cu 2þ ions, the stability of ascorbic acid can almost completely be preserved in contrast to aerobic conditions where ascorbic acid degrades rapidly (Boatright, 2016). The aim of the present study was to reveal oxygen availabilities in different media during heat treatment at 80 C and to understand the influence of Fe 3þ ions, ascorbic acid concentrations and temperature.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation